PEMBELAJARAN PPKN UNTUK PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR - Shania Alyfia Dany; Nazwa Alyah Putri; Naswaa Karimah; Arita Marini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
The character crisis in the Indonesian nation threatens the dignified character value of the nation for the Indonesian nation. Indonesia needs handling to solve the problems of the character of the Indonesian nation which has experienced a decline, especially in this era of globalization. Citizenship Education (Civics) is one of the subjects whose goal is to shape the character of the nation. Civics are required to be studied starting from the elementary, intermediate to higher education levels. This aims to shape the character of the Indoneisian nation. Pancasila values are formed based on the culture possessed by the Indoneisian people, thus, the character that should be attached to every Iindoneisiian natiion iis a characteir baseid on thei values of Pancasila in their daily life. That is why Civics are studied and applied to students since elementary school.